INTEGRATION OF LOCAL WISDOM AND INFORMATION TECHNOLOGY IN THE CIRCULAR ECONOMY IN THE ERA OF CLIMATE CRISIS AT THE ISLAMIC BOARDING SCHOOL IN JEMBER - Siti Masrohatin; Rini Puji (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study examines the implementation of circular economy principles at the microeconomic level through the integration of local wisdom and digital technology at Pondok Pesantren Jalaludin Ar-Rumi, Jenggawah. Using a qualitative phenomenological approach, data were collected through observation, interviews, and documentation. The study explores local wisdom–based practices aligned with the 3R strategy (reduce, reuse, recycle) and analyzes the role of YouTube as a medium for environmental education and documentation. The findings show that integrating circular economy practices, local wisdom, and digital technology effectively enhances sustainable resource management, resulting in a 70% reduction in organic waste, increased environmental awareness, and wider dissemination of environmental education. The circular economy is positioned as a pathway toward a low-carbon, resource-efficient, and socially inclusive economy that remains consistent with Islamic sharia principles. Keywords : Circular Economy, Local Wisdom, Information Technology